Human carnosinase 1 overexpression aggravates diabetes and renal impairment in BTBROb/Ob mice - Qiu, Jiedong; Albrecht, Thomas; Zhang, Shiqi; Hauske, Sibylle J.; Rodriguez-Nino, Angelica; Zhang, Xinmiao; Nosan, Darya; Pastene, Diego O.; Sticht, Carsten; Torre, Carolina de la; van Goor, Harry; Porubský, Štefan; et al. (Journal of molecular medicine, 2020)
To assess the influence of serum carnosinase (CN1) on the course of diabetic kidney disease (DKD).